Hilar cholangiocarcinoma associated with immunoglobulin G4‐positive plasma cells and elevated serum immunoglobulin G4 levels. Issue 4 (28th February 2018) - Azeem, Nabeel; Ajmera, Veeral; Hameed, Bilal; Mehta, Neil
Abstract : Unusual presentation of a patient with a hepatic mass meeting multiple criteria for IgG4‐sclerosing cholangitis but was ultimately found to be cholangiocarcinoma. Several published case reports describe patients with suspected cholangiocarcinoma who are later found to have IgG4‐sclerosing cholangitis, but few reports have demonstrated the reverse. Abstract : Immunoglobulin G4 (IgG4)‐related disease is a fibroinflammatory systemic disorder with multiorgan involvement. Proximal bile duct involvement results in IgG4‐related sclerosing cholangitis, which is characterized by a lymphoplasmacytic infiltrate with abundant IgG4‐positive plasma cells and fibrosis. Differentiating between cholangiocarcinoma and IgG4‐sclerosing cholangitis can present a diagnostic dilemma. We describe an unusual presentation of a hepatic mass meeting multiple criteria for IgG4‐sclerosing cholangitis but was ultimately found to be cholangiocarcinoma. Several published case reports describe patients with suspected cholangiocarcinoma who are later found to have IgG4‐sclerosing cholangitis, but few reports have demonstrated the reverse. Distinguishing between cholangiocarcinoma and IgG4‐sclerosing cholangitis is challenging, and a high clinical suspicion for cholangiocarcinoma must always be maintained. ( Hepatology Communications 2018;2:349‐353)